Double boron atom-doped graphdiynes as efficient metal-free electrocatalysts for nitrogen reduction into ammonia: a first-principles study. Issue 32 (10th August 2021) - Fu, Cheng; Li, Yafei; Wei, Haiyan
Abstract : Double boron atom-doped graphdiynes as efficient metal-free electrocatalysts for nitrogen reduction into ammonia: a first-principles study. Abstract : The electroreduction of dinitrogen (N2 ) is an attractive method for ambient ammonia (NH3 ) synthesis. In this work, double boron atom-anchored two-dimensional (2D) graphdiyne (GDY-2B) electrocatalysts have been designed and examined for the N2 reduction reaction (NRR) by density functional theory computations. Our calculations revealed that double boron atoms can be strongly embedded in a graphdiyne monolayer. In particular, configuration GDY-2B(S2 S2 ′) with two boron atoms substituting two equivalent sp-carbon atoms of diacetylene linkages exhibits excellent catalytic performance for reducing N2, with an extremely low overpotential of 0.12 V. The "pull–pull" mechanism imposed by doped double boron atoms is responsible for the magnificent effect of N2 activation. Besides, the competitive reaction of the hydrogen evolution reaction (HER) is suppressed owing to a large Δ G H* value of −1.25 eV. Based on these results, our study provides useful guidelines for designing effective double atomic catalysts (DACs) based on nonmetal 2D nanosheets for effective electrochemical reduction reactions.